Assisted techniques for vertebral cementoplasty: Why should we do it?. Issue 5 (May 2015) - Muto, M.; Marcia, S.; Guarnieri, G.; Pereira, V.
Abstract: Assisted techniques (AT) for vertebral cementoplasty include multiple mini-invasive percutaneous systems in which vertebral augmentation is obtained through mechanical devices with the aim to reach the best vertebral height restoration. As an evolution of the vertebroplasty, the rationale of the AT-treatment is to combine the analgesic and stability effect of cement injection with the restoration of a physiological height for the collapsed vertebral body. Reduction of the vertebral body kyphotic deformity, considering the target of normal spine biomechanics, could improve all systemic potential complications evident in patient with vertebral compression fracture (VCF). Main indications for AT are related to fractures in fragile vertebral osseous matrix and non-osteoporotic vertebral lesions due to spine metastasis or trauma. Many companies developed different systems for AT having the same target but different working cannula, different vertebral height restoration system and costs. Aim of this review is to discuss about vertebral cementoplasty procedures and techniques, considering patient inclusion and exclusion criteria as well as all related minor and/or major interventional complications.